Tingkat Kerusakan Hunian Akibat APG Erupsi Semeru di Desa Supiturang, Kabupaten Lumajang - Syuaibah, Aulia Rachmah; Balqis, Devina; Fitriana, Dhanar Dwi; Ramdlani, Subhan (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2024)
In Lumajang Regency, Indonesia, there are 11 potential natural disasters identified among 13 types of natural disasters. The eruption of Mount Semeru in 2021 was a significant disaster, resulting in extensive physical and non-physical damage. Supiturang Village is the area most impacted by the pyroclastic flow (APG) resulting from the activity of Mount Semeru. This study seeks to assess the extent of building damage resulting from the APG of the Mount Semeru eruption. This study employs a qualitative method. Data were gathered via field surveys and structured interviews. The observation centers on the upper, middle, and lower structures of the dwelling, with an emphasis on documenting and assessing the extent of damage. The findings of the study indicate that the housing at the study site remains susceptible to the risks associated with APG disasters in Mount Semeru.